Special operations forces and elusive enemy ground targets : lessons from Vietnam and the Persian Gulf War - Rosenau, William (MR (Series) ;, 2001)
In the Vietnam War and the Persian Gulf conflict, special operations forces (SOF) conducted reconnaissance operations to locate hidden targets when political and other considerations prevented the deployment of conventional ground units and air power alone was unable to locate and eliminate elusive objectives. In Vietnam, SOF teams crossed the border into Laos to search for truck parks, storage depots, and other assets along the Ho Chi Minh Trail that were obscured by jungle canopy and camouflage. In western Iraq, British and American SOF patrolled vast areas searching for mobile Scud launchers. In both cases, the nature of the terrain combined with adversary countermeasures made it extremely difficult for ground teams to achieve their objectives. There are a number of implications for future operations. Although new technology, such as mini- and micro-unmanned aerial vehicles, may make it easier to teams to reconnoiter wide areas, using SOF in this fashion is unlikely to achieve U.S. objectives. Concerns about casualties and prisoners of war are likely to limit the use of SOF to the most vital national interests. However, unattended ground sensors could play an enhanced role in future operations. Although most will be delivered by air, some will require hand emplacement in difficult enemy terrain, a mission well suited to SOF. SOF in a battle damage assessment role could help ensure that critical targets have been destroyed. Finally, SOF might disable, destroy, or recover nuclear, biological, or chemical weapons.